Reducing firearm access for youth at risk for suicide in a pediatric emergency department - Sofia Chaudhary; Sofia Chaudhary; Sofia Chaudhary; Kiesha Fraser Doh; Kiesha Fraser Doh; Kiesha Fraser Doh; Emilie Morris; Caroline Chivily; Donnetta S. Washington; Donnetta S. Washington; Scott E. Gillespie; Andrew Jergel; et al. (Frontiers Media S.A., 2024)
BackgroundFirearm-related suicide is the second leading cause of pediatric firearm death. Lethal means counseling (LMC) can improve firearm safe-storage practices for families with youth at risk of suicide.ObjectivesThis study aims to evaluate the feasibility of pediatric emergency department (ED) behavioral mental health (BMH) specialists providing LMC to caregivers of youth presenting with BMH complaints and to test for changes in firearm safety practices, pre-post ED LMC intervention, as measures of preliminary efficacy.MethodsProspective pilot feasibility study of caregivers of youth presenting to a pediatric ED with BMH complaints. Caregivers completed an electronic survey regarding demographics and firearm safe-storage knowledge/practices followed by BMH specialist LMC. Firearm owners were offered a free lockbox and/or trigger lock. One-week follow-up surveys gathered self-reported data on firearm safety practices and intervention acceptability. One-month interviews with randomly sampled firearm owners collected additional firearm safety data. Primary outcomes were feasibility measures, including participant accrual/attrition and LMC intervention acceptability. Secondary outcomes included self-reported firearm safety practice changes. Feasibility benchmarks were manually tabulated, and Likert-scale acceptability responses were dichotomized to strongly agree/agree vs. neutral/disagree/strongly disagree. Descriptive statistics were used for univariate and paired data responses.ResultsIn total, 81 caregivers were approached; of which, 50 (81%) caregivers enrolled. A total of 44% reported having a firearm at home, 80% completed follow-up at one week. More than 80% affirmed that ED firearm safety education was useful and that the ED is an appropriate place for firearm safety discussions. In total, 58% of participants reported not having prior firearm safety education/counseling. Among firearm owners (n = 22), 18% reported rarely/never previously using a safe-storage device, and 59% of firearm owners requested safe storage devices.At 1-week follow-up (n = 40), a greater proportion of caregivers self-reported asking about firearms before their child visited other homes (+28%). Among firearm owners that completed follow-up (n = 19), 100% reported storing all firearms locked at one week (+23% post-intervention). In total, 10 caregivers reported temporarily/permanently removing firearms from the home.ConclusionIt is feasible to provide LMC in the pediatric ED via BMH specialists to families of high-risk youth. Caregivers were receptive to LMC and reported finding this intervention useful, acceptable, and appropriate. Additionally, LMC and device distribution led to reported changes in safe storage practices.